HEALTH TEENAGER REPRODUCTION LEARNING THROUGH BIOLOGY SUBJECT IN STUDENT CLASS XI SMA N 1 LINGGO SARI BAGANTI PESISIR SELATAN REGENCY YEARS 2015 - Syaflindawati Syaflindawati Ridha Huday (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
The development of health reproduction in education institution is a precise strategy, considering most of student’s time are spending in the school. The researcher already did early observation with student and teacher, 60% student state Biology subject only talk a little about health reproduction, while 75% of Biology teacher state that in learning Biology, whwn talking about reprodution, student love to laugh and think that learn about reproduction is taboo. The aim of this research is to describe health teenager reproduction learning through Biology subject did by Biology teacher toward student class XI SMA N 1 Linggo Sari Baganti. The method of this research is qualitative with descriptive type. The technique in collecting data is through documentation, interview and observation. Analyzing data through data reduction, data presentation ang conclusion. The methode of taking informant in this research, is based on purposive sampling, which is Biology teacher that teach health production in class XI SMA N 1 Linggo Sari Baganti. The result of this research are: 1) in Biology subject class XI are found 7 RPP about health reproduction, 2) health reproduction learning is held with various method and learning strategic, 3) evaluation learning found that 20% student get outstanding marks, 60% student get excellent marks and 20% get good marks. In conclusion, health reproduction material already exist in Biology subject, the implementation of learning already did and evaluation learning with daily exam. Suggestion for school is to increasing extracurricular activity that related with the knowladge about health reproduction, give health promotion to student by appropriate speakers that related with health reproduction material and notice the factors that influence health reproduction and give impect to the students auch as envinonment, family, etc.